George Götz George spielt Heinrich George - George, Götz 1938-2016; Baumeister, Muriel 1972-; Finzi, Samuel 1966- (2013)
Dokudrama über den deutschen Schauspieler Heinrich George (1893 - 1946).
Orig.: D 2013
Keywords: George, Heinrich -- 1893-1946; Biografie; DVD-Video